Pengaruh Penetrasi Bank Asing Terhadap Struktur Persaingan Industri Perbankan Indonesia - Alexander Kevin dan Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This paper discussed the influence of foreign bank penetration on a particular scope of banking industry competition in Indonesia. The data used is from financial report and balance sheet from periode of 2002-2011 quarterly. The number of samples are 44 banks listed in Bank Indonesia. This research aims to examine whether the increasing number of foreign bank penetration affects the competition structure of banking industry in Indonesia, and examine whether the entry mode used by the foreign bank affects the competition structure of banking industry in Indonesia. The statistics used to analyze are non-linear least square to estimate non-linear model and ordinary least square to estimate the empiric model. Panzar Rosse statistic is used to estimate the dependent variable on the linear model. Panel data on non-linear model were used to identify foreign bank and estimate the competition level. Time-series data on the empiric model were used to measure banking industry competition that was affected by foreign bank penetration. This paper found that higher foreign penetration make the degree of banking competition tend to be more monopolistic. In addition, the researcher also found that the entry mode of penetration also affected the competition level. Penetration by merger and acquisition paths was proven to be more significant in affecting the competition in Indonesia compared to 'de novo' penetration.